Analytical model for textile reinforced mortar under monotonic loading - Filippou, Christiana; Chrysostomou, Christis (My University, 2020)
The recent evolution of using Textile Reinforced Mortar (TRM) as a sustainable and compatible solution for retrofitting masonry and heritage structures, requires the development of simplified models able to predict the behavior of this composite material in order to facilitate the implementation of numerical models of retrofitted structures using this technique, and further to create design guidelines for etrofitting structures using TRM. This paper presents a simple and easy to-implement tri-linear analytical model that correlates the mechanical properties and the geometric characteristics of the cement-based matrix and that of the textile reinforcement to define the stress–strain relationship of TRM under tensile load. The proposed nonlinear approach is based on the well-established Aveston–Cooper–Kelly (ACK) theory, which applies to fiber-brittle matrix, and extends it to textile cement-based matrix (TRM) using recommendations proposed by Eurocode 2 and by fib Model code 2010 for estimating the crack spacing, and the fracture energy of the composite material, respectively. TRM shows complex behavior in tension derived from the heterogeneity of its constituent materials (inorganic matrix and the fiber-textile). The proposed tri-linear analytical model proved accurate for predicting the stress–strain relationship of TRM under tensile loading, since the analytical curves properly fit the experimental results in almost any of the experimental case-studies that have been taken into consideration in the present study. A parametric study is also performed to examine the parameters that can influence the tensile behavior of TRM according to the proposed model.
Keywords: Textile; Inorganic-matrix composite; ACK theory; Crack spacing; Facture energy; Analytical modeling